2016
DOI: 10.1148/radiol.2016150852
|View full text |Cite
|
Sign up to set email alerts
|

Periventricular Nodular Heterotopia: Detection of Abnormal Microanatomic Fiber Structures with Whole-Brain Diffusion MR Imaging Tractography

Abstract: Advances in knowledge:1. Whole-brain Constrained Spherical Deconvolution (CSD) based fibre tractography and superresolution Track Density Imaging (TDI) mapping revealed abnormal fibre projections in nodular tissue suggestive of abnormal organization of white matter (with abnormal fibres both within nodules and projecting to the surrounding white matter) in patients with bilateral periventricular nodular heterotopia (PVNH).2. The detection of abnormal fibre structures by all four readers in all fourteen patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…Furthermore, in animals with experimentally induced PNH, it has been demonstrated that heterotopic neurons can form aberrant connections with the hippocampus, thereby giving rise to a complex epileptogenic network, data confirmed by a human case study . Tractography studies using diffusion‐weighted imaging in human subjects confirm aberrant projections suggestive of abnormal white matter organization . However, few human data are available using direct intracerebral EEG recording within distributed networks of NH, in terms of both resting state activity (interictal period) and seizure activity (ictal period).…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Furthermore, in animals with experimentally induced PNH, it has been demonstrated that heterotopic neurons can form aberrant connections with the hippocampus, thereby giving rise to a complex epileptogenic network, data confirmed by a human case study . Tractography studies using diffusion‐weighted imaging in human subjects confirm aberrant projections suggestive of abnormal white matter organization . However, few human data are available using direct intracerebral EEG recording within distributed networks of NH, in terms of both resting state activity (interictal period) and seizure activity (ictal period).…”
mentioning
confidence: 77%
“…31 The EI is a normalized quantity ranging from 0 (no epileptogenicity) to 1 (maximal epileptogenicity). This quantity may be estimated using a twostage procedure: (1) within a sliding window (5 s duration), the signal energy ratio (ER) is computed, between high (beta [12][13][14][15][16][17][18][19][20][21][22][23][24], gamma ) and low (theta [4-7.4 Hz] and alpha [7.4-12 Hz]) frequency bands of the EEG obtained from the signal spectral density C(w) (squared modulus of Fourier transform) (2) change-points in the ER[n] quantity, which is sensitive to frequency changes in the signal, are detected. An optimal algorithm ("cumulative sum algorithm" or "CUSUM") is used to automatically determine the time instant when ER[n] increases, that is, when theta alpha activity (predominant in background SEEG signals) changes into higher frequency activity (predominant during the rapid discharge).…”
Section: Seeg Contact Classification and Montage Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, fiber projections from periventricular heterotopias to distant neocortical areas are obviously sustained by nonanatomic pathways, even if they may cross them. 77 Moreover, patterns of increased connectivity related to the epileptogenic zone, coupled with decreased connectivity in widespread distal networks have been found, and are correlated to the severity and the duration of the disease. 78 Those pathologic networks may provide a benefit in terms of seizure-spreading limitation, but may also impair physiologic networks of the connectome and have a negative impact on function.…”
Section: Epilepsy Generates a Pathologic White Matter Plasticitymentioning
confidence: 99%
“…These pathologic organizations are described at a local level, as well as on long‐distance tracks, and are constituted of abnormal fiber tracts, distinct from the normal white matter anatomy. For instance, fiber projections from periventricular heterotopias to distant neocortical areas are obviously sustained by nonanatomic pathways, even if they may cross them . Moreover, patterns of increased connectivity related to the epileptogenic zone, coupled with decreased connectivity in widespread distal networks have been found, and are correlated to the severity and the duration of the disease .…”
Section: Awake Mapping For Epilepsy Surgery: When Epileptic Network mentioning
confidence: 99%